Clinical profile and pattern of Henoch-Schönlein purpura in children - Shah, Ganesh (Journal of Patan Academy of Health Sciences, 2015)
Introduction: This study was done to evaluate clinical profile of Henoch- Schönlein purpura (HSP) in children admitted in Patan Hospital. Methods: The medical records of all the children admitted in children ward with diagnosis of HSP from January 2008 to December 2015 were analysed for clinical presentation, management and outcome. Results: Of 59 patients, 37 (63%) were boys. The patients’ ages ranged from 15 months to 14 years with a mean of 8.3 years. Approximately, two third cases presented during winter and autumn. Upper respiratory tract infection preceded HSP in 37 and anti streptolysin O titer was positive in 6 of the 13 (46%) children tested at presentation. Skin purpura was seen in 59 (100%), arthritis or arthralgia in 48 (81%), gastrointestinal manifestation in 47 (80%) and renal involvement in 16 (27%). Forty-one (69%) patients received corticosteroid therapy. All the children made a full recovery, two with nephritis continued to have hypertension, hematuria and proteinuria. Symptoms occurred in 6 (10%) over a period one month to two years follow up. Conclusions: The HSP in children had seasonal occurrence, skin rash, pain abdomen with mild diseases and recovered well. Journal of Patan Academy of Health Sciences, Vol. 2, No. 1, 2015. page:17-21